Pararem Letter to Increase Community Legal Awareness in Apuan Traditional Village, Bali - I Ketut Sukadana; Luh Putu Suryani; Ni Made Puspasutari Ujianti (Community Service Journal of Law, 2022)
In society, the term customary law at the beginning of its birth was not widely known, what was known was only custom, but in that term the meaning of law was concluded but in many circles who did not understand customary law in depth they always questioned that custom is just a habit without legal elements. It is undeniable that a traditional village is a traditional village in Bali which has been autonomous since its inception. Each traditional village has its own management and assets, and has the authority to make awig-awig. The purpose of this program is to empower indigenous village communities so that they have a regulation in the form of pararem. The methods used in this service program are by giving lectures or legal counseling about the importance of a pararem in life in a traditional village,carrying out focus group discussions (FGD) on pararem design, and providing assistance in making traditional village pararem. The result shows that that the implementation of the community service program has succeeded in empowering the community and the program has been implemented properly. This is evident from the activities carried out in accordance with the stages that have been planned, namely legal counseling with the lecture method, conducting limited discussions (FGD), and mentoring. The assistance that has been carried out, partners are finally able to realize the pararem in the form of pararem penyahcah awig as many as 20 Pawos (articles). The success of this Pararem arrangement will indirectly increase public legal awareness.